Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) pada Baitulmaal Muamalat Medan - Astri Astri; Isra Hayati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The research was conducted at Baitulmaal Muamalat with the aim of knowing the effect of job satisfaction and organizational commitment on Organizational Citizenship Behavior (OCB) carried out by Baitulmaal Muamalat employees. This study uses quantitative methods and data collection is carried out using primary data derived from questionnaires. Research results reveal that job satisfaction has a positive influence on Organizational Citizenship Behavior (OCB) behavior. It is shown from the results of the t test where t count > t table (2,114 > 2.026) and a significance value of 0.041 <0.05. Organizational commitment variable also has a positive influence on Organizational citizenship behavior (OCB) where t count > t table (2,621 > 2.026) and a significance value of 0.013 <0.05. The results of the F test obtained that the variables of job satisfaction and joint organizational commitment significantly influence Organizational Citizenship Behavior (OCB) towards Baitulmaal Muamalat Medan where the Sig value is 0.008 <0.05. R2 test results R2 number of 0.232. This shows that 23.2% interest in Organizational Citizenship Behavior (OCB) is influenced by job satisfaction and organizational commitment Key Points: Job Satisfaction, Organizational Commitment, Organizational Citizenship Behavior (OCB)